Hydrochemical characteristics of groundwater and formation mechanism of Sr–rich mineral water in the Northern Carbonate Region, Yiyuan - Chen Sheng; Mingguo Wang; Peng Chen; Zitao Wang; Yangyang Min; Sichu Bai; Di Wu; Xianzhang Dang; Tong Li (Carbonates and Evaporites, 2026)

Mesoscopic-scale simulation of structural changes during mineral dissolution in coal: Coupled phase-field method verified by X-ray CT - Jiahao He; Baiquan Lin; Tong Liu; Zhenyong Zhang; Yanchi Liu (Advances in Water Resources, 2026)

Synthesis of a Novel FeOCl Loaded Activated Carbon/Graphene Oxide Composite Electro-Fenton Cathode for High Efficient Petrochemical Wastewater Treatment - Jiayi Wang; Huanhuan Xu; Haotong Sun; Jiaotong Liu; Haiming Yang; Xin Geng; Baigang An (Water, Air, & Soil Pollution, 2026)

Arbuscular mycorrhizal fungi recruit siderophore-producing phosphate solubilizing bacteria to mobilize sparingly soluble inorganic phosphate in subtropical orchard soils - Fengwa Zhu; Wei Zhang; Yongqiang Qin; Zengwei Feng; Yang Zhou; Xiaodi Liu; Qiutong Ling; Mingrong Deng; Honghui Zhu; Qing Yao (Applied Soil Ecology, 2026)

Trace element mobility and mineral-scale redistribution during retrograde metamorphism of lawsonite-bearing high-pressure rocks from Elekdağ, Turkey - Yu-Lu Tian; Jia-Min Wang; Gültekin Topuz; Aral I. Okay; Tong Liu (Contributions to Mineralogy and Petrology, 2026)

Environmental and Biological Factors Shaping Fish Swimming Ability: Insight From a Meta‐Analysis on Endemic Fish in China - Yuanming Wang; Hongtao Wang; Pengcheng Li; Xintong Li; Ruifeng Liang; Kefeng Li (Reviews in Aquaculture, 2026)
Fish swimming ability serves as a robust proxy for physiological assessment and species conservation. Numerous rivers with a large spatial span and diverse fish species in China complicate the efforts to understand swimming ability and challenge the protection of fish populations. One hundred and sixty‐four relevant studies over the past 15 years, involving 30 families and 126 distinct test sites, were identified to provide a comprehensive overview of fish swimming ability in China. Specifically, test sites geographically concentrated in the Yangtze River basin and Cyprinidae received the most research attention. The basin, family, altitude, living condition, and body length exerted considerable effects on fish swimming ability. Fish from the continental basin had the highest induced swimming speed ( U ind ), whereas those from the southwest basin showed outstanding critical ( U crit ) and burst ( U burst ) swimming speeds. U ind did not differ significantly at the family level, while Cyprinidae and Cobitidae outperformed other families in U crit and U burst . U ind was lowest at an altitude of 2328–3588 m, while U crit and U burst followed unimodal trends, peaking at altitudes of 622–1343 m. Test apparatus and protocols had a limited effect on fish swimming ability, only except that swimming speeds in Brett‐type flumes were higher than that in pipe channels or straight flumes. The living condition did not affect U ind while wild Cyprinidae exceeded cultured Cyprinidae in U crit and U burst . Overall, this study identified factors contributing to fish swimming ability differences and their variation patterns, deepening our knowledge on fish swimming ability and informing fish conservation strategies in China.

Characteristics of an NDM-1-producing Klebsiella pneumoniae strain belonging to ST105 - Wen Li; Yutong Liu; Yaxu Len; Li Xiang; Caixia Xin; Renjing Hu; Alberto J. Martín-Rodríguez; Bangqiong Weng; Yingshun Zhou (Antonie van Leeuwenhoek, 2026)

Quercetin induces molecular hallmarks of immunogenic cell death and cGAS-STING pathway activation via mitochondrial DNA release in hepatocellular carcinoma cells - Tong Lin; Yifan Chen; Zhengrong Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Multi-scale pore network approaches for predicting collector efficiency of colloids across a wide density range in soil hydrologic systems - Dantong Lin; Scott Alan Bradford; Yazhou Cao; Minpeng Tang; Baoqing Zhang; Liming Hu (Advances in Water Resources, 2026)

Effect of Eisenia foetida on enzyme activity and microbial community in phytoremediation of petroleum-contaminated soil using three plant species - Xiang Li; Junhua Hou; Jinjin Yang; Genwang Chang; Genmao Zhong; Junjie Wang; Tong Li; Shaokang Li (Applied Soil Ecology, 2025)